2021
DOI: 10.1039/d1dt00806d
|View full text |Cite
|
Sign up to set email alerts
|

Al2O3/CuI/PANI nanocomposite catalyzed green synthesis of biologically active 2-substituted benzimidazole derivatives

Abstract: The fabricated material Al2O3/CuI/PANI facilitates the synthesis of 2-substitued benzimidazoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…Our research group has earlier successfully fabricated multiple nanocatalysts to synthesize numerous biologically active organic frameworks such as benzimidazoles, polyhydroquinolines, xanthenes, 1,4-dihydropyridines, and 4Hpyrans. [39][40][41] In the present work, we design a novel, efficient, and magnetically recoverable Fe 3 O 4 @EDTA/CuI nanocatalyst to synthesize 2,3-dihydroquinazolin-4(1H)-ones through condensation of 2-aminobenzamide with different aldehydes. The surface of Fe 3 O 4 has been modied with ethylenediaminetetraacetic acid (EDTA) via the wet chemical method, and then the CuI is supported over the modied surface of the magnetic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has earlier successfully fabricated multiple nanocatalysts to synthesize numerous biologically active organic frameworks such as benzimidazoles, polyhydroquinolines, xanthenes, 1,4-dihydropyridines, and 4Hpyrans. [39][40][41] In the present work, we design a novel, efficient, and magnetically recoverable Fe 3 O 4 @EDTA/CuI nanocatalyst to synthesize 2,3-dihydroquinazolin-4(1H)-ones through condensation of 2-aminobenzamide with different aldehydes. The surface of Fe 3 O 4 has been modied with ethylenediaminetetraacetic acid (EDTA) via the wet chemical method, and then the CuI is supported over the modied surface of the magnetic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…However, these interactions can be various electrostatic interactions depending upon the nature of the precursor polymer. [ 91,92 ] For instance, aniline monomers are suspected of adsorbing on the MXene surface and between the MXene layers electrostatically. [ 93 ]…”
Section: Emerging Class Of Advanced Mxenes and Mxp Hncs For Air Conta...mentioning
confidence: 99%
“…However, these interactions can be various electrostatic interactions depending upon the nature of the precursor polymer. [91,92] For instance, aniline monomers are suspected of adsorbing on the MXene surface and between the MXene layers electrostatically. [93] Fu et al [94] reported similar observation information of graphene encapsulated Ti 2 CT x /PAN hybrid through cetyltrimeth ylammonium bromide (CTAB) assistance for super capacitor applications.…”
Section: Emerging Class Of Advanced Mxenes and Mxp Hncs For Air Conta...mentioning
confidence: 99%
“… 15 25 Another conventional method makes use of aldehydes, which led to the formation of the Schiff’s bases by condensation reaction with o -phenylenediamines, followed by cyclization and aerobic oxidation of the C–N bond to form the target compounds. 26 39 In addition, the metal-catalyzed oxidative 40 or acceptorless dehydrogenative 41 44 coupling of primary alcohols with o -phenylenediamines have also been proposed as effective synthetic methods for the preparation of benzimidazoles.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the most common methodologies for the synthesis of 2-subtituted benzimidazoles rely on using o -phenylenediamines as starting materials. The traditional synthesis involves the reaction of these reagents with carboxylic acid derivatives under strongly acidic conditions, sometimes at high temperature or under microwave irradiation. Another conventional method makes use of aldehydes, which led to the formation of the Schiff’s bases by condensation reaction with o -phenylenediamines, followed by cyclization and aerobic oxidation of the C–N bond to form the target compounds. In addition, the metal-catalyzed oxidative or acceptorless dehydrogenative coupling of primary alcohols with o -phenylenediamines have also been proposed as effective synthetic methods for the preparation of benzimidazoles.…”
Section: Introductionmentioning
confidence: 99%